THE EFFECT OF BEHAVIORAL AND PERFORMANCE ASPECTS OF EDUCATOR ACCOUNTANTS ON THE ACCOUNTING STUDENTS’ COMPETENCE - Denny Kurnia (Assets: Jurnal Akuntansi dan Pendidikan, 2021)
ABSTRACTThis study aims to determine the effect of behavioral and performance aspects of educator accountants on the competence of accounting students at universities throughout Banten Province. The method used is descriptive and associative quantitative. The results of the descriptive analysis showed that the behavioral aspect of the perception dimension variable had the highest average value, the lowest motivation dimension. The variable of educator accountants' performance of the collaboration dimension had the highest average value and the lowest of higher education Tridharma output quality dimension. The variable of accounting students' competence in the dimension of learning to live together has the highest average value, and the dimension of learning to understand is the lowest. The results of the associative analysis were obtained simultaneously that the behavioral and performance aspects of educator accountants affect the competence of accounting students. ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh aspek keperilakuan dan kinerja akuntan pendidik terhadap kompetensi mahasiswa akuntansi di Perguruan Tinggi se-Provinsi Banten. Metode yang digunakan adalah kuantitatif deskriptif dan asosiatif. Hasil analisis deskriptif diperoleh bahwa pada variabel aspek keperilakuan dimensi persepsi memiliki nilai rata-rata tertinggi, dimensi motivasi terendah. Variabel kinerja akuntan pendidik dimensi kerja sama memiliki nilai rata-rata tertinggi, dimensi kualitas output tridarma perguruan tinggi terendah. Variabel kompetensi mahasiswa akuntansi dimensi learning to live together memiliki nilai rata-rata tertinggi, dimensi learning to understand terendah. Hasil analisis asosiatif diperoleh secara simultan aspek keperilakuan dan kinerja akuntan pendidik berpengaruh terhadap kompetensi mahasiswa akuntansi.